A partial name prefix merging and shortening for name lookup in named data networking. Issue 7 (2nd October 2017) - Hsu, Jenq-Muh; Chang, Jui-Yang; Wang, Chih-Hung
Abstract : Purpose: Named Data Networking (NDN) is a content-centric network differing from the traditional IP-based network. It adopts the name prefix to identify, query and route the information content instead of IP-based addressing and routing. NDN provides a convenient way to access the content without knowing the originated location of the requested information. However, the length of name prefix varies. It is not like the fixed-length IP addresses that makes handling queries or searching the requested information in NDN easier. An efficient name lookup mechanism of name prefix will efficiently increase the performance of prefix identifying, name searching and content retrieving. Therefore, this paper aims to propose a partial name prefix merging and shortening scheme for enhancing the efficiency of name lookup in NDN. Design/methodology/approach: To reduce the work involved in name prefix identifying, querying, storing and routing, this work adopts a cyclic redundancy check-based encoding scheme to shorten the variable length of the name prefix into a proper and fixed length of encoded numerical information. In fact, the structure of a name prefix is presented in a combination of word segments with the slash symbol. The shortening procedure of name prefix can also be applied to adjacent word segments forming fixed-length encoded data for further efficiently matching the name prefix for name lookup in NDN. Findings: The experimental results show that the shorter length of encoded name prefix can effectively reduce the access time of name lookup and increasingly retrieve the corresponding named content in NDN. Through partial merging and shortening of name prefix, the length of encoded prefix name may be larger than the whole encoding of name prefix. It retains the information differences from different parts of various name prefixes. Thus, it can avoid collision problems with the same encoded information from various name prefixes. Originality/value: From the experimental results, it is observed that partial merging and shortening of name prefix is useful for name look up in NDN. It can increase the efficiency of name prefix matching and retrieving in NDN. It can also save memory space to store the name prefix in an NDN node.